CHARACTERISTICS OF USING PEDAGOGICAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Madaminova Sabina Alisher qizi (Journal of new century innovations, 2024)
Annotation: Nowadays it is very crucial learning languages as our nation is being developed day by day. So each pedagogue is responsible to teach foreign international languages within various techniques, methods as well as approaches. This article demonstrates characteristics of utilizing technologies in teaching foreign languages.